PERDA SYARIAH DALAM UPAYA PENINGKATAN DAYA SAING EKONOMI DAERAH - Muhtadi, Ridan (Fakultas Syariah, 2019)
The 2014 Law No. 24 makes regional governments have extensive authority in managing their regions. Using this authority, the implementation of regional regulation (perda) in Islamic Sharia is more suitable with Islamic local wisdom. Sharia regulations have indicated a change in legal politics, from the paradigm of legal unification to pluralism. More economists and practitioners are interested in sharia economic as alternative in preventing economic crisis after global financial crisis in 2008. As a result, some regions began to implement sharia economic by providing legal protection to formulate regional regulations. This study aims to analyze â€œperdaâ€ related to the implementation of Islamic Sharia by taking Sharia Economic and Financial Regulations as example. This is a juridical-normative research using primary and secondary legal data. The analytical approach used is content, concept, and case. The results indicate that Sharia Economic Regulations in Indonesia are very important. Moreover, the forecast growthof financial and sharia business industries is quite rapid in East Java. Hence, it isvery necessary to accelerate the divine economy to the regions and be able to create an economy in a stable and fair area.Undang-Undang No 24 Tahun 2014, menjadikan Pemerintah Daerah memilikikewenangan yang luas dalam pengelolaan didaerahnya. Dengan adanya kewenangan yang luas inilah, maka implementasi Peraturan Daerah (Perda) syariat Islam menjadi lebih sesuai dengan kearifan lokal yang islami. Perda syariah telah menunjukkan terjadinya perubahan politik hukum, dari paradigma unifikasi hukum menjadi pluralisme hukum. Krisis finansial global pada tahun 2008 semakin membuat ekonomi syariah dilirik banyak para ekonom dan praktisi sebagai salah satu alternatif pencegahan krisis ekonomi. Sehingga beberapa daerah mulai menerapkan ekonomi syariah dengan memberikan kepastian payung hukumnya dengan merumuskan peraturan daerah.